Comparison of shear test methods for evaluating the bond strength of resin cement to zirconia ceramic. (November 2014) - Kim, Jae-Hoon; Chae, Soyeon; Lee, Yunhee; Han, Geum-Jun; Cho, Byeong-Hoon
Abstract Objective. This study compared the sensitivity of three shear test methods for measuring the shear bond strength (SBS) of resin cement to zirconia ceramic and evaluated the effects of surface treatment methods on the bonding. Materials and methods. Polished zirconia ceramic (Cercon® base, DeguDent) discs were randomly divided into four surface treatment groups: no treatment (C), airborne-particle abrasion (A), conditioning with Alloy primer (Kuraray Medical Co.) (P) and conditioning with Alloy primer after airborne-particle abrasion (AP). The bond strengths of the resin cement (Multilink N, Ivoclar Vivadent) to the zirconia specimens of each surface treatment group were determined by three SBS test methods: the conventional SBS test with direct filling of the mold (Ø 4 mm × 3 mm) with resin cement (Method 1), the conventional SBS test with cementation of composite cylinders (Ø 4 mm × 3 mm) using resin cement (Method 2) and the microshear bond strength (μSBS) test with cementation of composite cylinders (Ø 0.8 mm × 1 mm) using resin cement (Method 3). Results. Both the test method and the surface treatment significantly influenced the SBS values. In Method 3, as the SBS values increased, the coefficients of variation decreased and the Weibull parameters increased. The AP groups showed the highest SBS in all of the test methods. Only in Method 3 did the P group show a higher SBS than the A group. Conclusions. The μSBS test was more sensitive to differentiating the effects of surface treatment methods than the conventional SBS tests. Primer conditioning was a stronger contributing factor for the resin bond to zirconia ceramic than was airborne-particle abrasion.